2007
DOI: 10.1002/hep.21675
|View full text |Cite
|
Sign up to set email alerts
|

X protein of hepatitis B virus functions as a transcriptional corepressor on the human telomerase promoter

Abstract: The X protein of hepatitis B virus (HBx) is essential for transactivation of hepatitis B viral and host cellular genes. It has been specifically implicated in the development of hepatocellular carcinoma; however, the molecular mechanism remains unknown. Telomeres, the DNA-protein complexes at the ends of eukaryotic chromosomes, protect chromosomes from degradation at the terminal regions, fusion with a broken DNA end, and inappropriate recombination. The shortening of telomeres that occurs during hepatocellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 60 publications
0
31
0
1
Order By: Relevance
“…HBx exhibits many activities in vitro. In a cell culture system, HBx is able to activate the transcription of host genes, such as c-Myc, as well as viral genes [5,6] . HBx is also involved in different cytoplasmic signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…HBx exhibits many activities in vitro. In a cell culture system, HBx is able to activate the transcription of host genes, such as c-Myc, as well as viral genes [5,6] . HBx is also involved in different cytoplasmic signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…MAZ has been implicated in the activation of a number of genes, including RAG-2, Adenovirus major late, (9,14,25,37,49,50,66,70,71,72). In addition, MAZ has been shown to repress its own gene, as well as c-myc, eNOS, Sp4, telomerase, and eosinophil-derived neurotoxin (28,34,57,60,62,69). Despite its abundant expression in skeletal and cardiac muscle (58,59), the functional role of MAZ in these tissues has not been explored, and to date, no MAZ knockout mouse has been described.…”
mentioning
confidence: 99%
“…When proapoptotic domain was deleted, truncated HBx had more telomerase induction activity than wild-type. Just as Su et al [26] pointed out, HBx isoforms decreased telomerase in the early stage of HCC, and HBx proteins increased telomerase activity in the development of carcinoma.…”
Section: Discussionmentioning
confidence: 94%
“…However, the effects of HBx on telomerase activity have been controversial. Su et al [26] found that some but not all HBx isoforms from chronic infection of HBV reduce telomere length by acting as a transcriptional corepressor of MAZ on the human telomerase promoter. Zhang et al [27] reported that the natural mutant of the HBx protein truncated 27 amino acids at the COOH terminal and wild-type HBx protein could stimulate the promoter transcriptional activities of hTERT in LO2 cells.…”
Section: Discussionmentioning
confidence: 99%